(untitled) (Semiárida, 2023)
Flood events are recurrent in the Pampas region. In the western portion, called the Pampas semi-arid region (RSP), periods of excess water alternate with droughts of varying duration. Floods produce negative consequences on the quality of life of the population, infrastructure and agricultural production. To develop mitigation strategies for these effects, it is important to know the dynamics of water excess. In this study, the spatio-temporal pattern of flooded surfaces in the last 27 years was determined in an area of 29,728 km2 of the RSP. The flooded areas were delineated based on interpretation of images from the historical series of the LANDSAT mission using automatic digitization techniques. One high-quality image per year (<10% cloud) was chosen for analysis. The flood regime was highly variable, where the maximum value in 2017 (5,153 km²) exceeded the minimum value recorded in 2009 (50 km²) by more than 100 times. Another major flood event was observed in the years 2001-2002 (1360 km²). The cyclical behavior of floods stands out with recurrence values close to 12 years. The duration of the water excess events was much shorter than the deficit events. The accumulated rainfall of 6, 12 and 24 months explains the flooded surfaces up to a threshold value above which large variations in waterlogging are observed in the face of stable rainfall values. This behavior was very evident in the water anomalies of 2016-2017. The waterlogging:precipitation relationship confirms the external contribution of water in extraordinary flood events. These contributions would correspond to the overflows of the Quinto River. On the other hand, the data obtained confirm the existence of a drainage basin from the north of the region in a northeasterly direction, which confirms the water connection with the Río Quinto water system. Actions to prevent the negative effects of floods require reliable predictive models. For the construction of these models it is necessary to consider the water contribution of the Río Quinto hydrological system, in addition to the precipitation regime. Director: Peinetti, Héctor Raúl